(untitled) (Comprehensive Journal of Science, 2026)
This study aims to measure the impact of electronic management on improving the efficiency of institutional performance in Libyan higher institutes, applied to the Higher Institute of Riqdalin. The study adopted the descriptive analytical method and used a questionnaire as the main tool for data collection from a purposive sample of the institute’s employees. The study found a positive, statistically significant relationship between the application of electronic management and the improvement of institutional performance efficiency, as electronic systems contributed to simplifying procedures, accelerating transaction completion, and improving work accuracy. The results also revealed a set of obstacles limiting the effectiveness of electronic management, most notably weak technical infrastructure, a lack of qualified human competencies, and resistance to organizational change. The study concluded with a set of practical recommendations to enhance the role of electronic management in improving institutional performance in higher institutes.